Interpersonal impressions of a social robot versus human in the context of performance evaluations. Issue 2 (3rd April 2021) - Edwards, Chad; Edwards, Autumn; Albrehi, Fatima; Spence, Patric
ABSTRACT: Extending previous research on the Computers Are Social Actors paradigm and the human-to-human interaction script, this study examines the interpersonal impressions of a social robot evaluator versus a human evaluator in a performance evaluation context. A between-subjects experiment was conducted to measure participants' impressions of the credibility, task and social attractiveness, and social presence of a social robot or a human evaluator of their public speaking performances. Additionally, participants rated the competence of the feedback they received. Both evaluators (human and social robot) garnered mostly "favorable" interpersonal impressions. Moreover, both agents' feedback was rated favorably. In all cases, the human evaluator was rated significantly higher than the social robot evaluator. Implications for the use of social robots in educational evaluator roles and for future human–robot interaction research are discussed.